1999
DOI: 10.1177/107319119900600108
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Perspectives and Practice Behaviors Involving Computer-Based Test Interpretation

Abstract: The debates of the 1980s regarding responsible use of computer-based test interpretation (CBTI) software have mostly disappeared, as CBTI use has become common practice. We surveyed 364 members of the Society for Personality Assessment to determine how they use CBTI software in their work and their perspectives on the ethics of using CBTI in various ways. Psychologists commonly use CBTI software for test scoring and to provide a complementary source of input for case formulations. Most do not use CBTI software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…This is consistent with guidelines issued by the American Psychological Association, as well as current assessment practices and conclusions from a review of the validity of computer-generated reports [13][14][15]. However, psychologists are almost evenly divided on the ethics of incorporating computer-generated text in psychological reports [14].…”
Section: Target Audiencesupporting
confidence: 54%
See 1 more Smart Citation
“…This is consistent with guidelines issued by the American Psychological Association, as well as current assessment practices and conclusions from a review of the validity of computer-generated reports [13][14][15]. However, psychologists are almost evenly divided on the ethics of incorporating computer-generated text in psychological reports [14].…”
Section: Target Audiencesupporting
confidence: 54%
“…This is intended to safeguard against uncritical acceptance by inadequately trained professionals who fail to recognize the limitations of computer-generated material [8][9][10][11][12]. This is consistent with guidelines issued by the American Psychological Association, as well as current assessment practices and conclusions from a review of the validity of computer-generated reports [13][14][15]. However, psychologists are almost evenly divided on the ethics of incorporating computer-generated text in psychological reports [14].…”
Section: Target Audiencementioning
confidence: 58%
“…The expectation is that professional psychologists and psychologists in training will be aware of the limitations of computer generated test interpretation, thereby reducing the likelihood of uncritical acceptance of such interpretation (Honaker CHB 1986) [14]; (Prince JP 1990) [15]. This is consistent with the conclusions of a survey of current assessment practices (McMinn A 1999) [16], as well as with a review of the validity of computer-generated psychological reports (Butcher PA 2000) [17], i.e., that such reports should supplement rather than replace clinical judgment. In keeping with this, the Assistant does not output directly to a printer, but rather to a rich text format (rtf) file to facilitate editing the results and merging them with other test and interview data.…”
Section: Target Audiencementioning
confidence: 58%
“…Furthermore, the Assistant produces statements based upon the statistical significance of differences between subtests which will not be accurate for versions which eliminate items. However, such restrictions may be insufficient, as psychologists are almost evenly divided on the ethics of using text generated by computers in reports written by psychologists [16].…”
Section: Target Audiencementioning
confidence: 99%
“…47-58). Survey data by McMinn, Ellens, and Soref (1999) indicated that 42% of psychologists rated this as generally unethical whereas 19% stated they did not know and 38% rated it as generally ethical (also McMinn, Buchanan, Ellens, & Ryan, 1999).…”
Section: Use Of Computer-based Narrativesmentioning
confidence: 99%